Implementasi Program Jemput Bola Administrasi Kependudukan (JEBOL ANDUK) Goes to School dalam Mempercepat Pelayanan Kartu Tanda Penduduk (KTP) Pemula - Ilham Wijaya, Muhammad; Hertati, Diana (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2025)
Surabaya, as the second largest metropolitan city in Indonesia with an area of 333.063 km² and a population of approximately 2.87 million, faces complex challenges in the implementation of population administration services. Data from the Surabaya City Population and Civil Registration Office (Dispendukcapil) in 2024 reveals a significant gap between targets and actual outcomes, where KTP ownership only reaches 46.68% of the eligible population. This condition indicates a discrepancy between public service theory which emphasizes accessibility and on-the-ground practices that remain hindered by conventional systems. This study aims to analyze the implementation of the "Jemput Bola Administrasi Kependudukan" (JEBOL ANDUK) Goes to School program in increasing KTP ownership among students at SMA Negeri 17 Surabaya, using George C. Edward III’s policy implementation theory. The research employs a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The main findings indicate that program implementation is not yet optimal in the aspect of communication, as the dissemination of information regarding the importance of KTP and population administration remains limited. On the other hand, the resource aspect has been effectively managed, supported by four trained officers and adequate facilities. The disposition aspect demonstrates a positive response, with participation from 156 students. Furthermore, the bureaucratic structure aligns with a flexible standard operating procedure (SOP). The results of this study suggest that although the JEBOL ANDUK Goes to School program has the potential to increase KTP ownership among students, improvements in communication strategies are necessary to achieve optimal and sustainable implementation.